AN ANALYSIS OF THE MAIN CHARACTERSâ CONFLICTS IN JANE AUSTEN NOVEL ENTITLED âSENSE AND SENSIBILITYâ - Hanna, Ina Daril (Universitas Islam Madura, 2016)
Conflict is not always happen between twoÂ person or more, but it also can happen with the environment, furthemore with our selves. Because sometime conflict is a problem that can not Â be seen factually. The existency of the conflict in a novel, it can attract the readers to read the contain of the whole page. Because they raise the curiousity of the readers. So that many the readers interest in reading novelÂ to know the ending of the story. It is also encouraged the researcher do this literary research. The title of this research is An Analysis of The Main Charactersâ Conflicts in Jane Austen Novel Entitled â SENSE AND SENSIBILITYâ. There are some conflicts occur in the novel, that is why the researcher want to analyze the conflicts of the main characters, Elinor and Marianne Dashwood. in order to know the main charactersâs problems face in the novel and also the solving problem in the novel. The researcher just focus on psychological conflict and social conflicts of the main characters. Hopefully this study can help the readers in understanding the conflicts that happened in the novel.